PENGARUH CARA MENGAJAR GURU TERHADAP HASIL PRESTASI SISWA - Niar Yuniarti (JENTRE, 2020)
The research departs from the belief that in addition to the teacher style in teaching the students, the teacher's learning style also affects the learning achievement students have gained. This research uses quantitative research. The research subject is 30 teachers of Madrasa in the Ministry of Religious Affairs who have followed a training. To support the research, questionnaire, interview, and observation were used as primary and secondary data. The results conclude that the teacher's learning style is much more visually compared to other styles of learning, the visual learning style focuses on vision. It shows that teacher learning styles have no correlation with the teacher's teaching style. In verificative analysis also gained the teacher's teaching style is lower to the student's learning outcomes.